UDTN-RS : A new underwater delay tolerant network routing protocol for coastal patrol and surveillance - Azad, Saiful; Mokthar Neffati, Ahmed Ali; Mahmud, Mufti R.; Kaiser, M. Shamim; Ahmed, Muhammad Raisuddin; Kamruzzaman, Joarder (Institute of Electrical and Electronics Engineers Inc., 2023)
The Coastal Patrol and Surveillance Application (CPSA) is developed and deployed to detect, track and monitor water vessel traffic using automated devices. The latest advancements of marine technologies, including Automatic Underwater Vehicles, have encouraged the development of this type of applications. To facilitate their operations, installation of a Coastal Patrol and Surveillance Network (CPSN) is mandatory. One of the primary design objectives of this network is to deliver an adequate amount of data within an effective time frame. This is particularly essential for the detection of an intruder's vessel and its notification through the adverse underwater communication channels. Additionally, intermittent connectivity of the nodes remains another important obstacle to overcome to allow the smooth functioning of CPSA. Taking these objectives and obstacles into account, this work proposes a new protocol by ensembling forward error correction technique (namely Reed-Solomon codes or RS) in Underwater Delay Tolerant Network with probabilistic spraying technique (UDTN-Prob) routing protocol, named Underwater Delay Tolerant Protocol with RS (UDTN-RS). In addition, the existing binary packet spraying technique in UDTN-Prob is enhanced for supporting encoded packet exchange between the contacting nodes. A comprehensive simulation has been performed employing DEsign, Simulate, Emulate and Realize Test-beds (DESERT) underwater simulator along with World Ocean Simulation System (WOSS) package to receive a more realistic account of acoustic propagation for identifying the effectiveness of the proposed protocol. Three scenarios are considered during the simulation campaign, namely varying data transmission rate, varying area size, and a scenario focusing on estimating the overhead ratio. Conversely, for the first two scenarios, three metrics are taken into account: normalised packet delivery ratio, delay, and normalised throughput. The acquired results for these scenarios and metrics are compared to its ancestor, i.e., UDTN-Prob. The results suggest that the proposed UDTN-RS protocol can be considered as a suitable alternative to the existing protocols like UDTN-Prob, Epidemic, and others for sparse networks like CPSN.